Digital Context Influences Batam Students’ Educational Ethics - Wijaya, Jonathan; Deu, Indasari; Tjahyadi, Surya (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
The rapid development of digital technology can cause serious problems, namely, the use of digital technology with an unethical attitude. The objective of this study is to analyze the use of digital technology can affect the unethical attitude of students in Batam city. By collecting 360 total data samples, all collected data will be analyzed using SPSS software by using extraction method: principal component analysis, factor analysis was conducted, and it was found that there are 3 factors: the development of the digital context has eliminated professional ethical attitudes, inappropriate use of digital technology, and the educational community's response to unethical attitudes. We conclude that the influence of the digital context with the development of digital technology can affect the unethical attitudes of Batam city students so that it requires provisions and policies from educational institutions to direct training to avoid the negative influence of the use of digital technology.Keywords: Digital Context; Digital Technology; Ethic; Principal Component Analysis AbstrakPerkembangan teknologi digital yang semakin pesat dapat menimbulkan masalah yang serius, yaitu penggunaan teknologi digital dengan sikap yang tidak beretika. Tujuan dari penelitian ini adalah untuk menganalisis penggunaan teknologi digital dapat mempengaruhi sikap tidak etis mahasiswa di kota Batam. Dengan mengumpulkan 360 total sampel data, semua data yang terkumpul akan dianalisis menggunakan perangkat lunak SPSS dengan menggunakan extraction method: principal component analysis: analisis faktor dilakukan, dan ditemukan bahwa ada 3 faktor: perkembangan konteks digital telah menghilangkan sikap etika profesional, penggunaan teknologi digital yang tidak tepat, dan respon komunitas pendidikan terhadap sikap tidak etis. Kami menyimpulkan bahwa pengaruh konteks digital dengan perkembangan teknologi digital dapat mempengaruhi sikap tidak etis mahasiswa kota Batam sehingga diperlukan ketentuan dan kebijakan dari institusi pendidikan untuk mengarahkan pelatihan agar terhindar dari pengaruh negatif penggunaan teknologi digital.